Correlation and Co-integration of BRIC Countries’ Stock Markets - Joshi, Sanjay S. (Indian Journal of Finance, 2013)
The relationship between the stock markets of developed countries and developing countries has been examined extensively in literature. However, stock markets of BRIC (Brazil, Russia, India and China) countries have received little attention separately despite the rapid growth and liberalization among these countries. So, the present study examines the relationship and co-integration of stock prices of BRIC countries’ stock markets. To investigate the relationships, the researcher examined the stock indices of BRIC countries and employed the daily closing price data (all converted in to Indian Rupees) in two different phases. The first phase was from April 2002 to March 2007 (Pre-crisis period); the second phase was from April 2007 to March 2012 (Crisis Period). However, the crisis period was actually till 2010, but to have an equal observation, the study used five years’ data. Stock price linkages were examined through Correlation analysis and the Engel Granger co-integration test was also used to study the long term equilibrium relationships. The results revealed that the Indian market has a strong positive correlation with Brazil and Russia, and further, India has a long term equilibrium relationship with China and Russia, which means that Investors have no diversification opportunity in these countries. Furthermore, the Indian market had no long term equilibrium relationship with Brazil, so the Indian investors have an opportunity to earn more in the Brazilian stock market.